(untitled) (Bangladesh Journal of Medical Science, 2016)
Wilsons disease is one of the most common inherited liver diseases with a worldwide incidence of 10-30 million cases. The increased frequency in certain countries is due to high rates of consanguinity and the fulminant presentation of the disease is more common in females than in males. It is an autosomal-recessive disorder caused by mutation in the ATP7B gene, with resultant impairment of biliary excretion of copper. Subsequent copper accumulation, first in the liver but later on in the brain and other tissues, produces clinical manifestations that may include hepatic, neurological, psychiatric, ophthalmological and other derangements. Genetic testing is impractical because of the multitude of mutations that have been identified, so accurate diagnosis relies on judicious use of laboratory and other diagnostic tests. Lifelong palliative treatment with a different combination of medications, or with liver transplantation if needed, can successfully ameliorate or prevent the progressive deterioration of the disease, otherwise death would inevitably ensue. Since effective treatment is available for this disease, early and correct diagnosis is very important. Here, we report a case of Wilsons disease in a 15-year-old girl presenting to us as chronic liver disease. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.495-498